Rancang Bangun Aplikasi Dilib-Us (Digital Library) Berbasis Android Menggunakan Metode Prototyping - Yustina Meisella Kristania; Joko Dwi Mulyanto (LPPM Universitas Bina Sarana Informatika, 2020)
Human life, both directly and indirectly, has been influenced by developments in the field of information and communication technology, one of which is in the library field. The library is one place where information and knowledge are easily obtained. But now libraries are still more often found in physical form where access to locations is still an obstacle. There are still many libraries that only provide a collection of printed books, making it difficult in the search process, and need more space to accommodate the collection of books. The manual lending and repayment process causes services to be less effective and efficient. The author tries to create an android application-based library system with the name Dilib-Us where there are search, loan and return features that can improve the quality of library services. This system applies the data collection method and prototype method as a system development model. The purpose of this study is to facilitate service users in finding information on libraries through the Dilib-Us application. It is expected that this application can provide facilities for prospective borrowers in the process of borrowing and returning books and for librarians in processing data, such as: adding, changing and deleting data.